PBX3 is essential for leukemia stem cell maintenance in MLL‐rearranged leukemia. Issue 2 (8th May 2017) - Guo, Huidong; Chu, Yajing; Wang, Le; Chen, Xing; Chen, Yangpeng; Cheng, Hui; Zhang, Lei; Zhou, Yuan; Yang, Feng‐chun; Cheng, Tao; Xu, Mingjiang; Zhang, Xiaobing; et al.
Abstract : Interaction of HOXA9/MEIS1/PBX3 is responsible for hematopoietic system transformation in MLL ‐rearranged ( MLL ‐r) leukemia. Of these genes, HOXA9 has been shown to be critical for leukemia cell survival, while MEIS1 has been identified as an essential regulator for leukemia stem cell (LSC) maintenance. Although significantly high expression of PBX3 was observed in clinical acute myeloid leukemia (AML) samples, the individual role of PBX3 in leukemia development is still largely unknown. In this study, we explored the specific role of PBX3 and its associated regulatory network in leukemia progression. By analyzing the clinical database, we found that the high expression of PBX3 is significantly correlated with a poor prognosis in AML patients. ChIP‐Seq/qPCR analysis in MLL ‐r mouse models revealed aberrant epigenetic modifications with increased H3K79me2, and decreased H3K9me3 and H3K27me3 levels in LSCs, which may account for the high expression levels of Pbx3 . To further examine the role of Pbx3 in AML maintenance and progression, we used the CRISPR/Cas9 system to delete Pbx3 in leukemic cells in the MLL‐AF9 induced AML mouse model. We found that Pbx3 deletion significantly prolonged the survival of leukemic mice and decreased the leukemia burden by decreasing the capacity of LSCs and promoting LSC apoptosis. In conclusion, we found that PBX3 is epigenetically aberrant in the LSCs of MLL ‐r AML and is essential for leukemia development. Significantly, the differential expression of PBX3 in normal and malignant hematopoietic cells suggests PBX3 as a potential prognostic marker and therapeutic target for MLL ‐r leukemia. Abstract : What's new? Acute myeloid leukemia (AML) with myeloid/lymphoid or mixed‐lineage leukemia ( MLL ) translocation constitutes a group of aggressive hematopoietic malignancies. The mechanisms by which MLL rearrangements mediate leukemic transformation, however, are not fully understood. In the present study, poor prognosis in AML patients was associated with elevated expression of the pre‐B‐cell leukemia homeobox 3 ( PBX3 ) gene. Moreover, PBX3 was found to be aberrantly regulated epigenetically in leukemia stem cells, while in leukemic mice, Pbx3 deletion significantly extended survival. The findings suggest that PBX3 serves a critical role in leukemia development and may be a potential prognostic marker for MLL ‐rearranged disease.